Daily rhythm of some haematological parameters in Holstein bovine maintained under natural conditions in southern hemisfere. Issue 2 (4th March 2019) - Scaglione, María Cristina; Cerutti, Raúl Delmar; Arfuso, Francesca; Rizzo, Maria; Pugliese, Michela; Piccione, Giuseppe
Abstract: The aim of this study was to evaluate the daily rhythms of haematological responses in bovines under different environmental conditions and to investigate the differences between bulls and cows. Twelve Holstein bovines were divided into two groups according to their gender: Group A (6 cows, 2 years, 500 ± 25 kg), and Group B (6 bulls, 2 years, 520 ± 25 kg). Environmental temperature and relative humidity were recorded and the temperature humidity index (THI) was calculated. Blood samples were collected every 3 h over 24 h period, every three months (winter, spring, summer, autumn) and analysed for haematological parameters. A significant effect of season ( p < 0.01) and of gender ( p < 0.05) on all studied parameters, and a circadian rhythm of RBC, Hb and Hct in all periods were found. These results may enhance the knowledge of haematological changes in cattles under natural environmental conditions, and their adaptation to the temporisations imposed by the environment.